Turbulence sets the length scale for planetesimal dormation: local 2D simulations of streaming instability and planetesimal formation - Klahr, Hubert; Schreiber, Andreas (The astrophysical journal, 2020)
The trans-Neptunian object 2014 MU69, named Arrokoth, is the most recent evidence that planetesimals did not form by successive collisions of smaller objects, but by the direct gravitational collapse of a pebble cloud. But what process sets the physical scales on which this collapse may occur? Star formation has the Jeans mass, that is, when gravity is stronger than thermal pressure, helping us to understand the mass of our Sun. But what controls mass and size in the case of planetesimal formation? Both asteroids and Kuiper Belt objects show a kink in their size distribution at 100 km. Here we derive a gravitational collapse criterion for a pebble cloud to fragment to planetesimals, showing that a critical mass is needed for the clump to overcome turbulent diffusion. We successfully tested the validity of this criterion in direct numerical simulations of planetesimal formation triggered by the streaming instability. Our result can therefore explain the sizes for planetesimals found forming in streaming instability simulations in the literature, while not addressing the detailed size distribution. We find that the observed characteristic diameter of ∼100 km corresponds to the critical mass of a pebble cloud set by the strength of turbulent diffusion stemming from streaming instability for a wide region of a solar nebula model from 2 to 60 au, with a tendency to allow for smaller objects at distances beyond and at late times, when the nebula gas gets depleted.